EKSPLORASI BAKTERI LOKAL PENGHASIL ANTIMIKROBA DI CAGAR ALAM TANJUNG API TELUK TOMINI SULAWESI TENGAH, INDONESIA - Alwi Millang; Widiawati; Umrah; Orryani Lambui (Biocelebes, 2021)
ABSTRACT Tanjung Api Nature Reserve is a headland located in Tomini Bay Ampana District Tojo Una-Una Regency, Central Sulawesi Province. This study aims to obtain local bacteria isolates as antimicrobial producers. The method used in this research is purposive sampling and screening method using "Agar Dua Lapis" (Double Layer Method). Testing antimicrobial potency using the method to make Well Diffusion (well) using three pathogens of microbial tests (S. aureus, E. coli, and C. albicans). In each well hole is given 500 μL of bacterial isolates each and incubated at a temperature of 37 oC for 24 hours and continued for 48 hours. The observed parameter is a clear zone formed around the well. Antimicrobial-producing bacteria screening results. obtained as many as 24 isolates of bacteria. Testing of antimicrobial potency by looking at the resulting inhibitory zone is obtained five isolates namely S2U1, S3U3, S7U3, S9U3, and S10U3 are the highest isolates of the bland zone of 12.25 mm but only against S. aureus, while S9U3 is the best isolate because it is able to inhibit the four test microbes namely S. aureus by 5.50 mm, E. coli 9.25 mm, and C. albicans 5.50 mm. Keywords: Exploration of bacteria, antimicrobials, and Nature Reserve